2013
DOI: 10.1097/imi.0000000000000029
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Minimally Invasive Pulmonary Vein Isolation for Lone Atrial Fibrillation

Abstract: Objective Minimally invasive surgical pulmonary vein isolation (SMI-PVI) is an emerging therapy for the treatment of symptomatic drug-refractory atrial fibrillation (AF). Nevertheless, the midterm and long-term results of SMI-PVI remain unknown. The aim of this retrospective multicenter study was to report on midterm efficacy and safety of SMI-PVI. Methods The study design was retrospective, multicentric, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…In the present series, no periprocedural bleeding was observed and, specifically, no LAAA related bleedings. This notwithstanding, LAAA related bleedings have been reported, due to the fragile and delicate wall of the LAAA [ 21 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the present series, no periprocedural bleeding was observed and, specifically, no LAAA related bleedings. This notwithstanding, LAAA related bleedings have been reported, due to the fragile and delicate wall of the LAAA [ 21 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…De Maat reported multicenter results of minimally invasive PVI in a cohort of 86 patients with 86% paroxysmal AF, median AF duration of 30 months, and mean LA diameter of 4.2 cm. In this near-ideal group of patients for stand-alone PVI, freedom from ATAs off AADs was 69% at three-year follow-up (34). A followup report that retrospectively matched a subset of these patients undergoing surgical PVI to a group of patients undergoing catheter PVI showed superior freedom from ATAs in the surgical PVI group at 12 months follow-up (88 vs. 41%, p<0.001) (35).…”
Section: B) Minimally Invasive Pulmonary Vein Isolationmentioning
confidence: 91%
“…We studied a series of patients who underwent sPVI as a first PVI procedure during the period of 2009–2011 in our university medical center. Inclusion criteria were highly symptomatic paroxysmal or early persistent AF, without concomitant cardiac structural disease, refractory to class I and/or class III antiarrhythmic drugs [ 2 ]. Exclusion criteria for surgical PVI were left atrial size > 55 mm (parasternal view), prior transcatheter PVI, prior heart or lung surgery, significant coronary disease or previous myocardial infarction, left ventricle hypertrophy > 12 mm, previous hospitalization for heart failure, left ventricular dysfunction (ejection fraction < 50%), moderate or severe mitral or aortic valve disease, or lung disease (prior tuberculosis or chronic obstructive pulmonary disease, GOLD classes III-IV).…”
Section: Methodsmentioning
confidence: 99%
“…In the recent years, thoracoscopic surgical pulmonary vein isolation (sPVI) has been added to the treatment of atrial fibrillation (AF). This technique has been shown to be safe and numerous studies have shown excellent efficacy outcome in paroxysmal and short-standing persistent AF due to high transmurality yielded epicardially by bipolar radiofrequency devices [ 1 , 2 ]. However, right ventricular (RV) function following sPVI has not been investigated.…”
Section: Introductionmentioning
confidence: 99%